A benchmark for particle-laden turbulent duct flow: A joint computational and experimental study. (November 2020) - Esmaily, M.; Villafane, L.; Banko, A.J.; Iaccarino, G.; Eaton, J.K.; Mani, A.
Highlights: Turbophoresis development length is 25–50 times the duct height. Turbophoresis requires O(1000) large-eddy turnover time to establish An algorithm is introduced for imposing a polydispersed particle mass flow rate. One-to-one comparison of clustering relies on replicating laser thickness in CFD. Collisions highly impact turbophoresis when volume fraction is as low as 3.9e−6. Abstract: A turbulent duct flow laden with small heavy inertial particles (Re τ  ≈ 570, St + ≈ 50, d p + ≈ 0.3, St ≈ 12, and d p / η  ≈ 0.17) is studied computationally and experimentally. We examine whether a long development section can be modeled using a short periodic domain. This simplification is not valid if the development section is too short (less than 25–50 duct-height in our case), the periodic simulation is not integrated long enough (less than O ( 1000 ) large-eddy turnover time in our case), or the effective mass loading ratio is not adjusted correctly (increased by a factor of 1.5 in our case). Additionally, we show that ignoring particle-particle collisions, even when the volume fraction is as low as 3.9 × 10 − 6, produces a large over-estimation of near-wall particle concentration (turbophoresis). The necessity of tailored post-processing of simulations for a one-to-one comparison against experiments is demonstrated. Namely, the finite thickness of the laser sheet and the optically-sampled volume size should be considered when post-processing simulations to reproduce the experimental measurement of clustering statistics. Experimentally and computationally, we show that an increase in the mass-loading ratio from 2.4% to 12% has a minimal effect on clustering, slightly lowers velocity fluctuations, and diminishes turbophoresis.